2007
DOI: 10.1002/cncr.22947
|View full text |Cite
|
Sign up to set email alerts
|

Candida and dysbacteriosis: A cytologic, population-based study of 100,605 asymptomatic women concerning cervical carcinogenesis

Abstract: Objective Decreased clearance of apoptotic cells is suggested to be a major pathogenic factor in systemic lupus erythematosus (SLE). The aim of this study was to investigate whether the binding of SLE autoantibodies to apoptotic cells influences the phagocytosis of these cells by macrophages. Methods Apoptosis was induced in a human T cell line (Jurkat) and a keratinocyte cell line (HaCaT) by ultraviolet B irradiation. Binding of purified IgG from 26 SLE patients and 15 healthy controls to apoptotic cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 57 publications
0
22
1
2
Order By: Relevance
“…The lack of an association observed here for BV with high grade cervical lesions differs from the positive association found in a previous study in an HIV-seropositive population in Finland [10], and in populations from Brazil, Holland, and South Africa, in which HIV-status was unrecorded [7][8][9]14]. Our results are consistent, however, with those from two European studies with HIV status unknown [13,15], and three studies in the US, two with unknown HIV-status [6,12] and one with HIV-seropositive participants [16].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The lack of an association observed here for BV with high grade cervical lesions differs from the positive association found in a previous study in an HIV-seropositive population in Finland [10], and in populations from Brazil, Holland, and South Africa, in which HIV-status was unrecorded [7][8][9]14]. Our results are consistent, however, with those from two European studies with HIV status unknown [13,15], and three studies in the US, two with unknown HIV-status [6,12] and one with HIV-seropositive participants [16].…”
Section: Discussioncontrasting
confidence: 99%
“…Although different methods were used to diagnose BV across studies (clinical diagnosis (pH >4.5, positive amine test, positive gram stain, and characteristic vaginal discharge) [9,12,13,15], gram stain [6,16], or from Pap slides [7,8,10,14]), in our view, the disparate association results do not appear to be explained by differences in methods to ascertain BV infection.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Roeters (2010) found the OR for Chlamydia and Gardnerella in high-grade smears are 7 and 12, respectively, and the OR for Trichomonas was also significantly high. Engberts (2007) reported the OR of Candida is 1.85 for LSIL and 2.0 for HSIL. We found that STIs significantly increases the risk of developing CIN 3.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that colonization rises in the luteal phase of the menstrual cycle (Engberts et al, 2007;Eschenbach et al, 2000;Odds et al, 1988); consequently, it is often thought to be associated with hormonal changes in the menstrual cycle. Several studies have documented point prevalence of vaginal colonization of Candida spp.…”
Section: Introductionmentioning
confidence: 99%